Korelasi Empiris Perpindahan Kalor Dua Fase (Air Udara) Aliran Kantung Gas dalam Pipa Horisontal Sirkular - Matheus M. Dwinanto (Jurnal Teknik Mesin (Sinta 3), 2011)
This research aimed at determining the heat transfer correlation of a heated non-boiling two phase flow consisting of air and water in a horizontal round pipe. The test section was a 24 mm ID cooper pipe with a length 1 m, and the heat transfer data a uniform wall heat flux boundary condition ranging from about 5968,17 to 10503,97 W/m2. From this research, it can be concluded that heat transfer coefficient of two-phase flow of bubble flow is increase as increase of gas superficial velocity and liquid superfisial velocity. The comparison deviation standart between heat transfer coefficient of two-phase flow experimental and heat transfer coefficient of two-phase flow correlation that proposed is 34%, but this deviation is still in limited value for experimental research.